Mixed-Potential Ammonia Sensor Based on a Dense Yttria-Stabilized Zirconia Film Manufactured at Room Temperature by Powder Aerosol Deposition - Nils Donker; Daniela Schönauer-Kamin; Ralf Moos (Sensors, 2024)
Powder aerosol deposition (often abbreviated as PAD, PADM, or ADM) is a coating method used to obtain dense ceramic films at room temperature. The suitability of this method to obtain ammonia mixed-potential sensors based on an yttria-stabilized zirconia (YSZ) electrolyte that is manufactured using PAD and a V2O5–WO3–TiO2 (VWT)-covered electrode is investigated in this study. The sensor characteristics are compared with data from sensors with screen-printed YSZ solid electrolytes. The PAD sensors outperform those in terms of sensitivity with 117 mV/decade NH3 compared to 88 mV/decade. A variation in the sensor temperature shows that the NH3 sensitivity strongly depends on the sensor temperature and decreases with higher sensor temperature. Above 560 °C, the characteristic curve shifts from exponential to linear dependency. Variations in the water and the oxygen content in the base gas (usually 10% oxygen, 2% water vapor in nitrogen) reveal a strong dependence of the characteristic curve on the oxygen content. Water vapor concentration variations barely affect the sensor signal.